Avis de tempête sur les Guyanes - Stéphen Rostain; François Renoux; Benjamin Iaparra Batista (IdeAs)
The history of climatic variations in Amazonia and their impact on the pre-Columbian world has long been ignored, due to a lack of solid data. The growth of interdisciplinary research since the turn of the millennium now makes it possible to better assess the links between climate and ancient cultural development. For example, the drier period that accompanied the medieval climatic anomaly (950-700 years BP) most likely had direct consequences on human settlement. In the Guianas, climate change, documented in the soil archives of the Cariaco Basin in Venezuela, may have been the ultimate driving force behind the decline of the coastal Arauquinoid peoples. This situation of climatic tension may indeed have provoked conflict in the centuries preceding European contact. This state of acute belligerence has remained ingrained in native collective memory. For example, the oral tradition of the Palikur people of French Guiana bears witness to great drought and to wars between them and the Kali’na before the arrival of Europeans. The historical accounts and myths that have been repeated for centuries are based on specific events that fit perfectly into a plausible reconstruction of the ancient past of the first inhabitants. The intersection of archaeological, ethnohistorical, paleoecological and paleoclimatological data opens up an original field of investigation, revealing little-known episodes in the early history of the indigenous Guianas.